Respuesta :

We are given equation:

5/6 x -2 = -2/3 x +1.

Note: when we have fracions in an equation, we always try to get rid fractions by removing denominator parts.

In the given equation we have 6 and 3 in denominator. So, we need to find the common denominator (lowest common denomiantor) of 6 and 3.

The lowest common denomiantor of 6 and 3 is 6.

So, equation is being multiplied by 6 on both sides.

Therefore,

Step 1) Multiply each side by LCD of fractions.

6 ( 5/6 x -2 ) = 6 (-2/3 x +1)

Step 2) Use distributive property to simplify above step, we get

6* 5/6 x = 5x

6 * -2 = -12

6 * -2/3 x = -4x and

6 * 1 = 6.

Therefore, we get

5x - 12 = -4x + 6 on simplifying second step.

Step 3) We use Addition property of Equality in third step.

Because we have -4x on right side, and the reverse operation of subtraction is addition.

5x - 12 = -4x + 6

+4x        +4x    Step 4) Here we just did simplification of above step.

____________________

9x -12  = 6

  +12   +12     Step 5) Again applied Addition property of Equality to get rid -12 from left side.  

_______________

9x  = 18         Step 6) Here we just did simplification of above step.

Step 7) Because 9 is being multiplied with x on left side. To get rid 9 from left side we need to apply reverse operation of multiplication.

Therefore, Division property of equality is used there by dividing 9 on both sides.

9x/9 = 18/9  

Step 8) Again did simplification of above step.

x=2 Final answer.

Answer:

We are given equation:

5/6 x -2 = -2/3 x +1.

Note: when we have fracions in an equation, we always try to get rid fractions by removing denominator parts.

In the given equation we have 6 and 3 in denominator. So, we need to find the common denominator (lowest common denomiantor) of 6 and 3.

The lowest common denomiantor of 6 and 3 is 6.

So, equation is being multiplied by 6 on both sides.

Therefore,

Step 1) Multiply each side by LCD of fractions.

6 ( 5/6 x -2 ) = 6 (-2/3 x +1)

Step 2) Use distributive property to simplify above step, we get

6* 5/6 x = 5x

6 * -2 = -12

6 * -2/3 x = -4x and

6 * 1 = 6.

Therefore, we get

5x - 12 = -4x + 6 on simplifying second step.

Step 3) We use Addition property of Equality in third step.

Because we have -4x on right side, and the reverse operation of subtraction is addition.

5x - 12 = -4x + 6

+4x        +4x    Step 4) Here we just did simplification of above step.

____________________

9x -12  = 6

 +12   +12     Step 5) Again applied Addition property of Equality to get rid -12 from left side.  

_______________

9x  = 18         Step 6) Here we just did simplification of above step.

Step 7) Because 9 is being multiplied with x on left side. To get rid 9 from left side we need to apply reverse operation of multiplication.

Therefore, Division property of equality is used there by dividing 9 on both sides.

9x/9 = 18/9  

Step 8) Again did simplification of above step.

x=2 Final answer.

Step-by-step explanation: